Peningkatan Hasil Belajar PAI Melalui Model Pembelajaran Problem Based Learning di Kelas IV UPTD SD Negeri 01 Durian Tinggi - Yeni Husna; Amelya Delina; Yulia Ningsih; Desri Wahyuni; Fadhila Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The background of this research is the low learning outcomes of students in the PAI subject, particularly in understanding the material on Asmaul Husna. The PBL method was chosen because it is believed to encourage students to be more active in the learning process, think critically, and solve problems independently. This study was conducted in two cycles, where each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of this study were 10 fourth-grade students. Data were collected through formative tests, interviews, and documentation, and analyzed descriptively both qualitatively and quantitatively. The results of the research indicate that the implementation of the PBL model successfully improved students' learning outcomes in the PAI subject, specifically in the Asmaul Husna material. The pre-cycle learning outcomes showed an average score of 68.5, with 50% of students meeting the learning criteria. In the first cycle, there was an improvement, with an average score of 77.6, and 70% of students meeting the learning criteria, although the target of 100% had not yet been reached. After revisions in the second cycle, most students were able to achieve the learning objectives, as seen in the students' average score of 92.0, with 90% of students successfully meeting the learning criteria. This improvement shows that the Problem-Based Learning (PBL) model can enhance student learning outcomes, especially in the Islamic Religious Education (PAI) subject for fourth-grade students at UPTD SD Negeri 01 Durian Tinggi.